Students’ Critical Thinking: The Effectiveness of Using a Global Warming E-book with PhET Interactive Simulation - Febri Tia Aldila; Jumadi; Siti Maryam Ulfa; Abidaturrosyidah; Nurdiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Technological developments have led to innovations in teaching materials such as the development of electronic books (e-books). In physics subjects, e-books need to be developed and used optimally to support learning. This research aims to determine the effectiveness of using physics e-books assisted by PhET interactive simulation based on problem-based learning in improving students' critical thinking skills on global warming material in modeling and implementation classes. This research is a quantitative research with a quasi-experimental research design with one pretest and posttest group. The subjects in this research consisted of 32 modeling class students and 23 implementation class students who were obtained using cluster sampling techniques. The data collection technique used is a test and the data analysis technique is the N-Gain test. The research results show that the use of physics e-books assisted by PhET interactive simulation based on problem-based learning on global warming material has an impact on increasing students' critical thinking abilities. Then, the use of physics e-books is quite effective (in the medium category) in improving students' critical thinking skills in modeling and implementation classes. The use of e-books in physics learning makes students more interested in learning so that it has an impact on students' thinking abilities.